Narrative abilities in individuals with Down syndrome: single case-profiles - Neitzel, Isabel (Frontiers in Psychology, 2023)
Introduction: Narrative abilities are an important part of our everyday lives and social interaction with others. Nevertheless, narration is a complex ability influenced by language and cognition. This makes it difficult for individuals with language and cognitive impairment, such as in children and adolescents with Down syndrome. Previous studies have shown distinct narrative impairments in individuals with Down syndrome; nevertheless, this research was based on overall group means in most cases. To identify individual strengths and weaknesses and to draw conclusions for speech and language therapy, the narrative profile of every participant should be considered equally. Following this approach, the current study aims to describe single case narrative profiles in individuals with Down syndrome.Method: The narrative transcripts of 28 children and adolescents with Down syndrome (aged 10;0-20;1), based on a non-verbal picture book, were rated using the Narrative Scoring Scheme across seven macro-and microstructural categories. Point scores across the whole group are displayednevertheless, the paper specifically addresses the individual narrative profiles of the participants. The participants could be assigned to narrative profile groups which show different characteristics, strengths and weaknesses. Group comparisons and correlations were computed for the relation to language abilities (especially vocabulary) and nonverbal cognitive abilities.Results: The results of the two profile groups with minimal and developing narrative skills differ significantly not only concerning narrative outcomes in the Narrative Scoring Scheme but also for language abilities and developmental stage of nonverbal cognition. Individuals that show floor effects in narrative abilities are characterized by an overall weakness in language and cognition. In contrast, a group of approximately equal size shows distinct strengths in their narrative profiles which are in line with their vocabulary strengths, MLU and nonverbal cognition.Discussion: The current study uses a new approach to identify individual narrative profiles in a group of individuals with Down syndrome. The results of the investigation underline the existence of narrative impairments in many individuals with Down syndrome but also point to individual strengths of the participants. Furthermore, the study outcomes suggest that narration might be representative for overall language and cognition in individuals with Down syndrome. However, intervention studies are missing.